Occupational and Environmental Challenges for Women. Issue 4 (April 2023) - Lindberg, Briana; Rerucha, Caitlyn; Givens, Melissa
Abstract: The prevalence of women in the global workforce is increasing. Women increasingly participate in nontraditional employment settings in previously male-dominated industries and manually intensive professions, such as military service, emergency response, health care, aviation, space, agriculture, and technical trades. Limited occupational and environmental hazard data specific to women exist for these work environments. Physiologic and biomechanical differences between sexes create unique workplace challenges specific to women. This article will summarize challenges confronting women working in nontraditional employment and identify strategies to mitigate risk within these populations.